2016
DOI: 10.1590/0103-6440201601014
|View full text |Cite
|
Sign up to set email alerts
|

Low-Fusing Porcelain Glaze Application on 3Y-TZP Surfaces can Enhance Zirconia-Porcelain Adhesion

Abstract: The aim of this study was to assess whether surface treatment improves zirconia-porcelain adhesion. The 3Y-TZP blocks were cut into squares, then polished and sintered. The zirconia surface treatments were performed as follows: no treatment (C); tribochemical silica coating (TBS); glaze application + hydrofluoric acid etching (GA); glaze application + hydrofluoric acid etching + silanization (GAS); deposition of silica nanofilm (NF). After treatments, veneering porcelain cylinders (3.3 x 3.3 mm) were built up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(38 citation statements)
references
References 22 publications
3
34
0
1
Order By: Relevance
“…The increased demand for esthetic restorations has caused the growing use of zirconia as an infrastructure material for single fixed or multiple prostheses; however, the literature has frequently noted chipping and failure of bonding between zirconia/veneer as one of the principal faults in unsuccessful metal‐free restorations created with zirconia . This fact propelled the development of numerous studies in search of more effective surface treatments, with the objective of increasing the strength of the zirconia bond with veneering ceramic . The null hypothesis formulated in this study was rejected, since a significant difference was found for the bond strength values between the treated and untreated specimens, favorable to surface‐treated groups.…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…The increased demand for esthetic restorations has caused the growing use of zirconia as an infrastructure material for single fixed or multiple prostheses; however, the literature has frequently noted chipping and failure of bonding between zirconia/veneer as one of the principal faults in unsuccessful metal‐free restorations created with zirconia . This fact propelled the development of numerous studies in search of more effective surface treatments, with the objective of increasing the strength of the zirconia bond with veneering ceramic . The null hypothesis formulated in this study was rejected, since a significant difference was found for the bond strength values between the treated and untreated specimens, favorable to surface‐treated groups.…”
Section: Discussionmentioning
confidence: 85%
“…In relation to the method of specimen manufacturing, some studies did not clarify the method used. Among those that did, five studies manufactured specimens through CAD/CAM systems, one study used manual methods, with the help of carborundum discs, while others manufactured their specimens with high‐precision machines (ISOMET, MicroSlice). The size and format of the specimens varied according to the tests performed for each study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations